Cross-cultural Perspectives on Political Language: A Comparative Review of Thai and American Discourses with Implications for Critical Society - Koomwongthai, Peeradej (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2025)
With rhetorical, persuasive, and manipulative features of communication, political language has been a research interest in political science, linguistics, sociology, anthropology, and discourse analysis to the present day. The current article aims to shed light on cross-cultural attributes of political language by comparing Thai and American cultural perspectives with a brief, comparative overview by adopting theoretical frameworks in rhetorical devices, Aristotle’s proofs of appeal (1952), and Hofstede’s cultural value dimensions (2001). Given the fact that the language used in this context is perceived as an influential instrument of persuasion and manipulation, political language represents a rich repertoire of convincing messages delivered via speeches, debates, official replies, and announcements to communicate with citizens and people in specific society and the world at large. Of particular interest is an intertwined relationship between language and culture. The current article provides a brief overview of previous and contemporary literature on rhetorical discourse, persuasive proofs of appeal, and cultural value dimensions across intercultural boundaries. The topics of review and discussion are presented as follows: 1) rhetorical overviews; 2) analytical approaches to political language studies; 3) intercultural perspectives on discussion; and 4) summary and implications. This article can be beneficial for extensive cross-cultural communication studies with better understanding on persuasive messages as critical receivers towards society.